Analysis of Problems in the Production of Knitted Products - Ulugboboeva MM; Usmanov R. (Genius Journals, 2022)
The weight of knitted clothes is constantly increasing. This is due to the high serviceability and economic efficiency of knitted goods. The continuous growth of the production of chemical fibres, especially synthetic yarns, and the rapid development of knitting production techniques greatly contributed to the development of the knitting industry. This article discusses the problems of the development of the knitwear industry in Uzbekistan
Keywords: constructive; canvas; wardrobe; symbol